Offering a choice of daily and event-driven preexposure prophylaxis for men who have sex with men in the Netherlands: a cost-effectiveness analysis. (1st August 2021) - van Hoek, Albert Jan; Reitsema, Maarten; Xiridou, Maria; van Sighem, Ard; van Benthem, Birgit; Wallinga, Jacco; van Duijnhoven, Yvonne; van der Loeff, Maarten Schim; Prins, Maria; Hoornenborg, Elske
Abstract : Objectives: To assess the cost-effectiveness of a preexposure prophylaxis (PrEP) programme offering a choice of daily and event-driven PrEP for men who have sex with men (MSM) in the Netherlands. Methods: We used an agent-based transmission model and an economic model to simulate a programme offering only daily PrEP and a programme offering daily and event-driven PrEP. Use of PrEP medication and preference for daily versus event-driven PrEP were estimated from the Amsterdam PrEP Demonstration Project (AMPrEP). We calculated costs, quality-adjusted life-years (QALY), and incremental cost-effectiveness ratios (ICER), over 2018–2027. An ICER less than [Euro sign]20 000 per QALY gained was considered cost-effective. Results: Using AMPrEP data, we estimated that 27% of PrEP users chose event-driven PrEP with a median of 12 pills per month; daily PrEP users used a median of 30 pills per month. With PrEP, 3740 HIV infections were averted and 1482 QALYs were gained over 2018–2027, compared to the scenario without PrEP. The probability of the PrEP programme being cost-effective (compared to not having a PrEP programme) increased from 91% with daily PrEP to 94% with a choice of daily and event-driven PrEP. The probability of being cost-saving increased from 42% with only daily PrEP to 48% with choice of daily and event-driven PrEP. Conclusions: A daily PrEP programme for MSM would be cost-effective. Providing a choice of daily and event-driven PrEP can result in savings and is more likely to be cost-effective and cost-saving, compared to a programme offering only daily PrEP. Abstract : Supplemental Digital Content is available in the text